Comparative efficacy and safety of imrecoxib versus celecoxib: a systematic review and meta-analysis - Zeng, Xian; Dai, Lilin; Li, Zude; Dong, Xiaomin; Liao, Zengzhen; Chen, Liji; Tan, Yuan; Chen, Wei (Frontiers in Pharmacology, 2026)
ObjectiveThis meta-analysis aimed to compare the analgesic efficacy, anti-inflammatory effects, and safety profiles of the selective cyclooxygenase-2 (COX-2) inhibitors imrecoxib (IMR) and celecoxib (CEL), providing evidence-based guidance for clinical drug selection.MethodsA systematic search was conducted of English and Chinese databases through August 2025 to identify randomized controlled trials (RCTs) comparing IMR and CEL. Methodological quality was assessed using the Cochrane Risk of Bias (ROB 2.0) tool, and quantitative analyses were performed using R software. Primary outcomes included clinical response rate, pain intensity assessed by the visual analog scale (VAS), and the overall incidence of adverse events (AEs). Secondary outcomes focused on serum inflammatory markers (CRP and ESR) and disease activity (BASDAI) in patients with axial spondyloarthritis (axSpA).ResultsPooled analyses found no significant differences between IMR and CEL in clinical response or pain reduction, indicating comparable analgesic efficacy. The overall safety profiles of the two drugs were also similar. Notably, in the osteoarthritis (OA) subgroup, IMR was associated with a significantly lower incidence of adverse events compared with CEL. An exploratory subgroup analysis in axSpA patients suggested that IMR may offer potential advantages over CEL in improving inflammatory markers and disease activity. However, this finding is based on a few small trials and should be interpreted with caution due to the low certainty of evidence.ConclusionIMR demonstrated comparable efficacy and overall safety to CEL, supporting its role as a viable alternative selective COX-2 inhibitor in clinical practice. IMR may have potentially favorable anti-inflammatory effects in axSpA. The observed anti-inflammatory advantage of IMR in axSpA remains to be confirmed. Given the limitations of small sample sizes, short follow-up durations, and incomplete safety reporting, further large-scale, high-quality RCTs are warranted to validate these findings.Systematic Review Registrationidentifier CRD420251243032.